The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9ra03601f
|View full text |Cite
|
Sign up to set email alerts
|

On the road to cost-effective fossil fuel desulfurization byGordonia alkanivoransstrain 1B

Abstract: The utilization of desulfurizing microorganisms that can grow in low nutrient culture media without vitamins and other growth promoters (e.g. yeast extract, peptone) is an advantage for BDS upgrade since it may reduce the biocatalyst production costs significantly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The enhancement of DBT‐BDS using Gordonia alkanivorans strain 1B has been previously reported, applying the agro‐industrial waste sugar beet molasses as a carbon source, recording a growth rate of 0.0795 h −1 and 2‐HBP production of 250 μmol L −1 5 . Total reducing sugars in Jerusalem artichoke juice have been reported to duplicate the BDS efficiency of G. alkanivorans strain 1B 8 . The agro‐industrial waste carob pulp liquor has been also reported as a cost‐effective carbon source for BDS 62 …”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…The enhancement of DBT‐BDS using Gordonia alkanivorans strain 1B has been previously reported, applying the agro‐industrial waste sugar beet molasses as a carbon source, recording a growth rate of 0.0795 h −1 and 2‐HBP production of 250 μmol L −1 5 . Total reducing sugars in Jerusalem artichoke juice have been reported to duplicate the BDS efficiency of G. alkanivorans strain 1B 8 . The agro‐industrial waste carob pulp liquor has been also reported as a cost‐effective carbon source for BDS 62 …”
Section: Resultsmentioning
confidence: 68%
“…5 Total reducing sugars in Jerusalem artichoke juice have been reported to duplicate the BDS efficiency of G. alkanivorans strain 1B. 8 The agro-industrial waste carob pulp liquor has been also reported as a cost-effective carbon source for BDS. 62…”
Section: Optimization Of Different Physicochemical Operational Conditions Of Dbt-bds Batch Processmentioning
confidence: 99%
See 2 more Smart Citations
“…BDS is more efficient and less expensive than the remaining methods as HDS in removing sulfur from refractory heterocyclic compounds present in crude oil, it could be used in oil refineries as a complement to achieve ULSD. Indeed, BDS can be used to desulfurize heavy oils, as shale oils, which have high thiophene concentration [ 8 ].…”
Section: Introductionmentioning
confidence: 99%